Risk Management in the PPP Scheme for the East Sumatra National Ring Road Preservation Project in Riau Province - Papua, Munarlis; Jayady, Arman; Nurjaman, Hari Nugraha (International Journal Labs, 2025)
The East Sumatra Highway, particularly the Pekanbaru–Simpang Lago section in Pelalawan Regency, is a strategic route that supports national economic growth and is part of the National Road network, which experiences congestion due to heavily loaded vehicles. As the need for road infrastructure intensifies, the government faces limitations in the State Revenue and Expenditure Budget (APBN). Therefore, alternative financing mechanisms such as State Sharia Securities (SBSN) and the Government and Business Entity Cooperation (PPP) scheme are required. This study aims to identify and assess the risks in the East Sumatra National Road Preservation PPP Project using a type-1 questionnaire-based descriptive analysis approach. The research respondents consist of representatives from the Party in Charge of the Cooperation Project (PJPK) and the Implementing Business Entity (BUP). The results indicate that PJPK faces 63 risks, with the main classifications including location, design, construction, operations, revenue, political, financial, force majeure, sponsorship, interface, asset ownership, and strategy. Meanwhile, BUP faces 60 risks under similar classifications, except that location risks fall solely under the responsibility of PJPK. These findings highlight the importance of proportional risk sharing according to the authority and responsibilities of each party. This research contributes to the development of risk mitigation strategies and supports decision-making for PPP-based infrastructure project financing. For future research, the use of the fuzzy logic method is recommended to reinforce risk weight allocation and to broaden the respondent base from both parties, thereby producing more representative results.